Association between Self Reported Questionnaire-determined Physical Activity Level with the Cardiorespiratory Fitness in Adolescent - Chandrawati Gultom; Irma Ruslina Defi; Ellyana Sungkar (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Cardiorespiratory fitness (CRF) and physical activity (PA) in childhood can reduce the risk of cardiovascular diseases in adults. Further analysis related to the relationship between PA and CRFto prevent an inactive lifestyle is neededMethods: An analytic cross-sectional design in adolescents aged 13-15 years old, who had no cardiovascular and metabolic diseases, with light or medium physical activity, no deformity in thelower limbs and posture disorders. Cardiorespiratory fitness was assessed by the indirect method Bruce Protocol in the Faculty of Sport and Health Education’s library, The University of Pendidikan Indonesiaon September-October 2019. Physical activity was measure by the Physical Activity Questionnaire for Adolescent (PAQ-A).Results: Subjects consisted of 82 adolescents (41 boys, 41 girls), aged 13-15 years old with the Body mass index (BMI) was 18.5-29 kg/m2. The mean value of predicted VO2max (Bruce) for boys and girlswere 46.66 ± 8.765 and 40.06 ± 6.210 ml/kg2, while the value of predicted PAQ-A score for boys and girls were 2.54±0.756 and 2.16±0.416. The correlation between PAQ-A and VO2max in boys and girlswere r=0,190, p=0,234 and r=0.420; p=0.006.Conclusion: There was a moderate association between PAQ-A with VO2max in girls.Keywords: Cardiorespiratory fitness, Physical activity questionnaire, VO2max.